Modelos gêmeos em teorias de campos escalares - Dantas, Joseclécio Dutra (2012)
In this work we do an investigation of new features of so-called k-defects, which are topological defects with non-canonical kinetic term. Specifically, we study a class of k-defects in models of scalar field theories distinct from standard theory but discribing, case to case, the very same defect structure with the very same energy density as that described by the theory governed by standard Lagrange density. In teories which presents such relationships, distinct models support the same topological structure; why call them of twinlike models. We then build a model of twin theory, which we call ALTW model, and find the relationships between them, including relations between the potentials of both, which, although distinct, they present minima that are connected by the same field solution, for the case of static and stable configurations. The results are ilustrated with several examples. In order to distinguish between theories, we analyze the situation in which the component T11 of the energy-momentum tensor is nonzero, which is equivalent to breaking the pressureless condition required to ensure stability of static solutions. With the same purpose of distinction, we did a study of linear stability of defects and we found that, although representing the same defect structure, case to case, a theory is not a simple reparametrization of the other. We also made an extension of the twin nature between more general models of real scalar field theries and an application to braneworld scenario. We also investigated the behavior twin between standard and tachyonic models in FRW cosmology, where the scalar field evolves over time.